Household Search or Individual Search: Does It Matter? - Flabbi, Luca; Mabli, James (Journal of Labor Economics, 2018)
Most labor market search models ignore the fact that decisions are often made at the household level. We fill this gap by developing and estimating a household search model with on-the-job search and labor supply. We find that ignoring the household as a decision-making unit has relevant empirical consequences. In estimation, the individual search model implies gender wage offer differentials almost twice as large as the household search model. In the application, the individual search model implies female lifetime inequality 30% lower than the household search model. Labor market policy effects on lifetime inequality are also sensitive to the specification.